Two new Idiocera Dale from the Mediterranean (Diptera: Limoniidae) - Starý, Jaroslav (Zootaxa, 2020)
Two new species of Idiocera (Idiocera) Dale, 1842 are described, viz. I. (I.) falcistylus sp. n. (Spain) and I. (I.) cretopunctata sp. n. (Greece: Crete), and their wings and male terminalia are illustrated. A key to the European species of the subgenus is appended.